Meningkatkan Kemampuan Operasi Pembagian Melalui Coolmath4kids bagi Peserta Didik Disabilitas Rungu (Single Subject Research di Kelas V SLB Serasi Kota Payakumbuh) - Newa, Dwi Ambar; Damri, Damri; Marlina, Marlina; Efrina, Elsa; Nasri, Yosa Yulia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is based on the real conditions at SLB Serasi in Payakumbuh City, where a hearing-impaired student in the eighth grade is still unable to perform division operations. Therefore, the researcher attempts to use multimedia through the website coolmath4kids to help improve the students' understanding. This study aims to determine the improvement of division operation skills through coolmath4kids for hearing-impaired students. Quantitative approach was applied in this study with experimental method in single subject research (SSR) type A-B design, the results showed significant improvement. At the initial stage of Baseline (A) which was carried out for four observations and obtained a presentation of stability of 40% each. After being given Intervention through coolmath4kids in six observations, students' abilities increased with a percentage of 70%, 90%, 90%, 100%, 100% respectively. Thus, coolmath4kids is proven to be able to improve division operations in learners with hearing disabilities.